Factors Influencing The Use Of Accounting Information On SMEs In Padang - Ayu, Melati Sukma; Andriani, Wiwik; Sukartini, Sukartini (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study examines and analyses the factors that influence SMEs to use accounting information in their business. The method of determining the sampling in this study using purposive sampling. The type of data used in this study is primary data obtained through distributing research questionnaires to SMEs in the city of Padang. Data analysis techniques using multiple regression analysis and tested by t-test. The results of this study indicate that the level of education and accounting knowledge has a positive effect on the use of accounting information on SMEs. At the same time, business experience and entrepreneurial spirit do not affect the use of information systems in SMEs in Padang City.